2013
DOI: 10.1371/journal.pone.0062383
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-449a Enhances Radiosensitivity in CL1-0 Lung Adenocarcinoma Cells

Abstract: Lung cancer is the leading cause of cancer-related mortality worldwide. Radiotherapy is often applied for treating lung cancer, but it often fails because of the relative non-susceptibility of lung cancer cells to radiation. MicroRNAs (miRNAs) have been reported to modulate the radiosensitivity of lung cancer cells and have the potential to improve the efficacy of radiotherapy. The purpose of this study was to identify a miRNA that can adjust radiosensitivity in lung adenocarcinoma cells. Two lung adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 50 publications
3
27
0
Order By: Relevance
“…Cells were used for experiments when they were around 60% to 70% confluent. Preferably, low passages (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were used. Irradiation assay Radiosensitivity assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were used for experiments when they were around 60% to 70% confluent. Preferably, low passages (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were used. Irradiation assay Radiosensitivity assay.…”
Section: Methodsmentioning
confidence: 99%
“…miRs playing a role in radioresistance have been described, although experiments were done in cell line pairs and not in a larger panel of cell lines (18)(19)(20).…”
Section: Radioresistance Of Head and Neck Cancermentioning
confidence: 99%
“…Xiang' et al showed that microRNA-98 could sensitize cisplatin-resistant human lung adenocarcinoma cells by up-regulation of HMGA2 [23]. Liu and his colleagues reported that microRNA-449a could enhance radiosensitivity in CL1-0 lung adenocarcinoma cells [24]. However, the roles of miR-409-3p in LAD progression remain unclear and need to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified some novel miRNAs which are involved in the DNA repair pathway and regulate the DNA damage response to radiation (29)(30)(31). Yan et al (32) identified miR-101 as a molecule able to sensitize cancer cells to IR by targeting the 3'UTR of DNA-PKcs and ATM transcripts.…”
Section: Discussionmentioning
confidence: 99%